2017
DOI: 10.1136/thoraxjnl-2017-210134
|View full text |Cite
|
Sign up to set email alerts
|

Delayed neutrophil apoptosis enhances NET formation in cystic fibrosis

Abstract: BackgroundCystic fibrosis (CF) lung disease is defined by large numbers of neutrophils and associated damaging products in the airway. Delayed neutrophil apoptosis is described in CF although it is unclear whether this is a primary neutrophil defect or a response to chronic inflammation. Increased levels of neutrophil extracellular traps (NETs) have been measured in CF and we aimed to investigate the causal relationship between these phenomena and their potential to serve as a driver of inflammation. We hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
149
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(160 citation statements)
references
References 53 publications
(52 reference statements)
5
149
0
2
Order By: Relevance
“…The observation that corticosteroids lead to a prolonged lower level of NETs in recovering patients who have a better outcome does perhaps suggest a beneficial role for NETosis during the process of recovering from pneumonia, and would be in keeping with other recent data suggesting that patients who survive sepsis may indeed have a greater ability to make NETs than non-survivors [24]. Recent data from CF patients has suggested that a delay in neutrophil apoptosis in these subjects leads to an increased ability to form NETs [21], suggesting that the activation of alternative routes of disposal for neutrophils may have consequences in terms of promoting inflammation. Indeed the fact that corticosteroids are known to delay neutrophil apoptosis may be of direct consequence in the present study by preferentially allowing NETosis in those treated with prednisolone.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The observation that corticosteroids lead to a prolonged lower level of NETs in recovering patients who have a better outcome does perhaps suggest a beneficial role for NETosis during the process of recovering from pneumonia, and would be in keeping with other recent data suggesting that patients who survive sepsis may indeed have a greater ability to make NETs than non-survivors [24]. Recent data from CF patients has suggested that a delay in neutrophil apoptosis in these subjects leads to an increased ability to form NETs [21], suggesting that the activation of alternative routes of disposal for neutrophils may have consequences in terms of promoting inflammation. Indeed the fact that corticosteroids are known to delay neutrophil apoptosis may be of direct consequence in the present study by preferentially allowing NETosis in those treated with prednisolone.…”
supporting
confidence: 68%
“…NETs have been associated with inflammation in a number of sterile inflammatory conditions such as systemic lupus erythematosus, rheumatoid arthritis, small vessel vasculitis, gout and cardiovascular disease [19], underlining a role for NETs in inflammation, although the role of NETs in the inflammatory response to infection is less well defined. Crucially the mechanisms by which NETs can promote inflammation are now being revealed and recent evidence suggests that the interaction of NETs with macrophages may be key to this [20,21]. Therefore, NETs may have a crucial role to play in the crosstalk between cells of the innate (and adaptive) immune system, promoting inflammation, whereas other forms of neutrophil disposal such as apoptosis have a defined role in driving the resolution of inflammation [22].…”
mentioning
confidence: 99%
“…In this later situation, NETs are more likely to be harmful and contribute to the immunopathology in the CF airway. Gray et al demonstrated that CF neutrophils formed more NETs and lived longer due to decreased apoptosis than did non‐CF neutrophils . The opposite was found in people with G551D who were being treated with ivacaftor.…”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 99%
“…The opposite was found in people with G551D who were being treated with ivacaftor. The investigators also found that NETs provided a pro‐inflammatory stimulus to macrophages, which was enhanced in CF . The CF lung is an especially conducive environment for NETosis.…”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 99%
“…During the release of NETs, the plasma membrane ruptures in a programmed manner. This suggests that the formation of NETs involves a suicide programme, morphologically different from other types of cell death, such as apoptosis and necrosis . One form of programmed cell death, necroptosis, can result in cytolysis.…”
Section: Mechanisms Of Neutrophil Extracellular Trap Formationmentioning
confidence: 99%